(untitled) (American Journal of Islam and Society, 2009)
The story of Muhammad’s night journey to Jerusalem and ascent to heaven enjoys huge popularity across the Muslim world. It has functioned as a vehicle for many forms of artistic expression throughout the ages as well as having been subject to much literary development. In addition, it has impacted and interacted with legal and theological dogma that may be seen in elements ranging fromthe establishment of the five daily prayers (on which see the fascinating essay by Ron Buckley, “The Isra’/Mi`raj and the prescription of the five daily prayers,” in Andreas Christmann, Robert Gleave [eds.], Studies in Islamic Law: A Festschrift for Colin Imber [Oxford: Oxford University Press, 2007], 23-49) to the conceptualization of paradise and hell (see the treatment in Nerina Rustomji, The Garden and the Fire: Heaven and Hell in Islamic Culture [NewYork: Columbia University Press, 2008], especially pp. 26-39). Historically, the narrative makes its basic appearance in some of the earliest Muslim texts, for example, in Ibn Ishaq’s eighth-century work entitled Life ofMuhammad. The emergence of the story has been seen (in, for example, Brooke Olson Vuckovic, Heavenly Journeys, Earthly Concerns: The Legacy of the Mi`raj in the Formation of Islam [New York and London: Routledge, 2005]) as an important element in the historical formation of Islamic identity; it has also been seen by some as having had a powerful impact on European imaginings of the hereafter, as found in medieval writers such as Dante ...